Vestibular disorders in patients after COVID-19 infection - Pazdro-Zastawny, Katarzyna; Dorobisz, Karolina; Misiak, Paula; Kruk-Krzemień, Anna; Zatoński, Tomasz (Frontiers in Neurology, 2022)
Introduction: The COVID-19 clinical symptoms relate primarily to the respiratory system but may also involve many other, including the nervous system. Recently vertigo or dizziness have been described as one of the clinical manifestations and possible complication of COVID-19. Material and methods: This clinical study was designed to describe the otorhinolaryngologic evaluation and VNG (videonystagmographic) findings in patients with an antecedent of COVID-19 infection in the last 6 months. In this study, we sought to investigate the presence of persistent vestibular damage in healed COVID-19 patients and to determine the origin of vertigo conducting comprehensive vestibular examination. To evaluate the association precisely, otoneurologic assessement was conducted in all participants. Study group included 58 patients aged 23 to 75 years with vertigo, who were diagnosed with COVID-19 infection 6 months before examination. Each participant was submitted to an evaluation consisting of anamnesis, otorhinolaryngological evaluation and videonystagmography (VNG). Results: Spontaneous nystagmus with closed eyes was reported in 8 patients (13.8%). Positional nystagmus was observed in 15 patients (24.1%). Asymmetrical optokinetic nystagmus was observed in 18 patients (31%) A distorted record in the tracking pendulum test was present in 23 patients (39.7%), square waves in 34 COVID-19 patients (58.6%). Unilateral weakness was observed in 23 subjects (39.7%); among those with unilateral weakness, 22 patients (95.7%) also demonstrated directional preponderance contralateral to the UW. Another 16 patients (27.6%) presented only directional advantage. The post-caloric recruitment was present in 38% patients. Conclusions: Patients who had been diagnosed with COVID-19 seens to be more likely to suffer from vertigo/dizziness and to compensate more slowly. Covid-19 infection may cause inner ear damage and lead to vestibular dysfunction. The role of the cetral nervous system in the onset of equilibrium disorders should be considered. Presence of vertigo of central origin may indicate the neurotropic effect of Sars-Cov2 following COVID-19. Imbalance may be the only symptom of COVID-19 and may also be a late complication of the disease due to post-infectious inflammation of the nervous tissue. Comprehensive studies are needed to investigate whether COVID-19 can cause long-term vestibular deficits.